(untitled) (Hematology Meeting Reports, 2009)
Unconjugated monoclonal antibodies, particularly rituximab, are now an important part of the treatment of B-cell lymphoma. The use of radiolabeled antibodies offers a different way to deliver radiotherapy and take advantage of the well known radiosensibility of lymphoma. Radio-immunotherapy (RIT) is defined as a treatment modality in which cytotoxic radiation is delivered to tumour cells via antibodies binding to tumour-specific or tumour-associated antigen. The antibody serves as transporter for the radioisotope and participates on its own in the tumour killing. The advantage of conjugated radiolabeled antibody over unconjugated antibody is that there is no need to target every to achieve an antitumour effect. Tumour with low or heterogeneous antigen expression, as poorly vascularised and bulky tumour can also be killed by the cross-fire of neighbourhood targeted cells.